On the problem of ultrasonic diagnosis of a wrong formation of the hip joint in infants of the 1st year of life - Kutsenok, Yakov; Vovchenko, Ganna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The authors attracted attention to an insufficient level of training specialists in ultrasonic diagnostics and, proceeding from experience of Germany, suggest health care establishments concrete measures in order to eliminate defects in diagnosing the state of the hip joint in children, especially infants during their first year of life.